Incorporating Online Pictorial Images in Upgrading EFL Students in Understanding Specific Text - Rina Angraini; Baharuddin Baharuddin (UICELL, 2022)
Teaching EFL students is a daunting task. Based on the preliminary study, the EFL students had an insufficiency in understanding the meaning that had caused them to misinterpret in understanding the specific text. This study aims to investigate how the utilization of online pictorial images improves students’ accuracy on domain-specific knowledge and how it plays a role in developing students’ when dealing with specific text. Thus, it may create a suitable teaching method for the English for Telecommunication I course. First-semester students in the academic year 2022/2023 who enrolled in English for Telecommunication I course at Politeknik Negeri Padang participated in this study. The qualitative method is used to analyze the data generated through the interviews to present and identify the role of online pictorial images in upgrading students’ understanding of specific knowledge. The results uphold that using online pictorial images plays important role in upgrading students' understanding of the specific text.   Keywords: EFL, online pictorial images, specific text, teaching and learning process